Pendampingan Literasi Lingkungan Pengelolaan Sampah di Panti Asuhan Putri Aisyiyah Jember - Latifa Mirzatika Al-Rosyid; Sawitri Komarayanti; Wulan Gurtino; Pramesya Ramadhana Arifin (Indonesian Journal Publisher, 2023)
The growth in the number of people affects the production of waste that is not processed properly. Indiscriminate disposal of waste results in environmental pollution which will have an impact on other lives. In addition, the low level of public awareness in sorting waste according to its type contributes to environmental pollution. The existence of these problems certainly requires an innovation that can support and increase public awareness, especially from an early age, in waste management. This Stimulus Community Partnership Program (PKMS) activity is one of the strategies to provide literacy assistance in waste management to the younger siblings of the Putri Aisyiyah Jember Orphanage. Understanding regarding the importance of protecting the environment, the dangers of waste if it is not managed properly, needs to be given early, from an early age. The waste management literacy assistance consists of several activities, including: socialization of the dangers of waste, its types, material value for waste (4R) reduce, reuse, recycle and replace, then ends with activities of sorting garbage around the orphanage and grouping according to type . This PKMS activity has been completed, so that it reaches the evaluation stage of the entire process of community service activities. The results of the evaluation of the younger siblings: they were greatly helped by the existence of these activities as for increasing literacy in keeping the environment clean and not disposing of waste in an inappropriate place. Appreciation was also given by the managers of the girls' orphanage who were grateful for helping people care about their own environment. It is hoped that the community will begin to be aware of the effectiveness of waste management in the future.